The TILs-US score on ultrasonography can predict the pathological response to neoadjuvant chemotherapy for human epidermal growth factor receptor 2-positive and triple-negative breast cancer. (May 2022) - Kimura, Yuri; Masumoto, Norio; Kanou, Akiko; Fukui, Kayo; Sasada, Shinsuke; Emi, Akiko; Kadoya, Takayuki; Arihiro, Koji; Okada, Morihito
Abstract: Background: The tumor-infiltrating lymphocyte (TIL)-ultrasonography (US) score determined through characteristic US findings has predictive performance of lymphocyte-predominant breast cancer (LPBC). This study aimed to investigate whether the TIL-US score before neoadjuvant chemotherapy (NAC) can predict the pathological complete response (pCR). Methods: We evaluated patients with human epidermal growth factor receptor type 2 (HER2)-positive breast cancer (n = 55) and triple-negative breast cancer (TNBC) (n = 24) who underwent surgery after NAC from November 2012 to April 2019. Pre-NAC biopsy examination was performed to examine stromal TILs; the cutoff value for predicting pCR was defined as ≥50% stromal TILs. The TILs-US score was calculated from the pre-NAC US findings. Based on previous data, the cutoff value for predicting pCR was set at ≥4 points. Results: Forty-six patients achieved pCR. The TIL-US score was significantly associated with the pCR rate ( p = 0.003) but not the pre-NAC biopsy findings ( p = 0.055). Multivariate logistic regression analysis revealed that a TILs-US score ≥4 and HER2 positivity were significant pCR predictors (odds ratio [OR] 3.69; p = 0.031; OR 8.74; p = 0.025). Conclusions: TILs-US scores can be used to evaluate the therapeutic effect of NAC, and may be used as a non-invasive, convenient, and an alternative method to assess stromal TILs in pre-treatment biopsies. Highlights: TILs-US score has predictive performance for lymphocyte-predominant breast cancer. TIL expression correlate with response to NAC for breast cancer. TILs-US score predicts the therapeutic effect of NAC in HER2-positive breast cancer and TNBC.